(untitled) (Raparin Journal of Humanities (RJH), 2024)
This study aims to identify the level of the language development among preschool children in Shahrazor district from the perspective of teachers, and it is relationship to some of the variables: Gender, social status of the child’s family, birth sequence, family size and economic status. Used A measure from the study (Al-Dardir et al., 2016) consisting of (58) items, and it was applied to (89) children male and female from the kindergarten, the measure was answered by kindergarten teachers which is the number of the all teachers in the Shahrazor District. The study used the descriptive analytical approach and the study tool were consisted of language development. The study result showed that the level of language development among the children of Shahrazour district is weak in the total degree, and was there area of language development, the field of verbal communication has received the first grade,Then followed by the field of readiness for reading (pre-reading skills) ranked second, and followed by the field of comprehension ranked third, then readiness for writing (pre-writing skills) came in the fourth rank. In addition, the study results indicated that there were no statistically significant differences between the average degrees of the level of language development in due to the variables: gender of the child, the social status of the child’s family, the birth sequence and the economic status of the family. In addition to a set of recommendations and two suggestions for language development of pre-school children.